Gender-divide and a Turbulent Society - Prasad, Dr. K Kannan (SMART MOVES JOURNAL IJELLH, 2025)
This article is a translation of a research article by N Shankar Narayanan that has been cited below. This translation has not been published in any journals, book or magazine and it is the original translation of the article written by the author. The author of the article has consented for the translation and publication of the same. Women have always been at the receiving end when a society is tumultuous, in spite of the scientific and technological advances it boasts of. jfdk; [“Thaganam”] (2001) is a Tamil novel by Andal Priyadarshini portrays such concerns. A 21st century family may not survive the financial burden it poses if both the husband and wife do not take up a job. It becomes a necessity that the act of a man opposing the idea of a woman taking up a job , just as a mental perception that is bent on being patriarchal. In such a society, the idea of man proving himself to be one, only if he gets a job, needs to be eradicated. By breaking such a social construct, a society should tame itself to focus only on the fact whether the family fetches enough money while the husband and the wife takes up a job. The resultant of such a social construct can be observed when a working woman consents to marry a man who earns more than her. Further, a society should also question when a woman does not receive the same wage that man gets for the same kind of job. Both the gender should formulate ways, together to fight sexual harassment at work. Finally, in a turbulent society, a woman can lead her life peacefully only if punishment for sexual abuse and harassment are made severe in court of law and sex education being given properly to the members of the society.